İş tatmini ve örgütsel bağlılık arasındaki ilişki: bir uygulama - Kaya, Nilay (My University, 2013)
Tatmini, Örgütsel Bağlılık ÖZET İŞ TATMİNİ VE ÖRGÜTSEL BAĞLILIK ARASINDAKİ İLİŞKİ: BİR UYGULAMA Bu tez çalışmasında iş tatmini ve örgütsel bağlılık arasındaki ilişki incelenmiş ve kesitsel çalışmaya yer verilmiştir. Otomotiv sektöründe faaliyet gösteren firmanın tüm çalışanlarına uygulanan anket sonuçlarına göre, iş tatmini ve örgütsel bağlılık arasında anlamlı bir ilişki tespit edilmiştir. Bireylerin örgütsel bağlılık alt boyutları olan duygusal bağlılık, devam bağlılığı ve toplam örgütsel bağlılık düzeyleri arttıkça iş tatmini alt boyutları olan içsel doyum, dışsal doyum ve genel doyum düzeylerinin de arttığı saptanmıştır. Çalışmada ayrıca iş tatmini ile örgütsel bağlılık düzeylerinin demografik faktörlere bağlı olarak değişip değişmediği belirlenmeye çalışılmıştır. İş tatmini düzeyleri ile yaş, medeni durum, öğrenim durumu, şimdiki işyerinde çalışma süresi ve toplam çalışma süresi faktörleri arasında anlamlı bir ilişki tespit edilmezken, cinsiyet, aylık ücret ve pozisyon ile iş tatmini düzeyleri arasında anlamlı bir ilişki tespit edilmiştir. Örgütsel bağlılık düzeyleri ile cinsiyet, yaş, medeni durum ve şimdiki işyerinde çalışma süresi faktörleri arasında anlamlı bir ilişki tespit edilmezken, öğrenim durumu, toplam çalışma süresi, aylık ücret ve pozisyon ile iş tatmini düzeyleri arasında anlamlı bir ilişki tespit edilmiştir. Job Satisfaction, Organizational Commitment

THE RELATIONSHIP BETWEEN JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT: AN APPLİCATION This study examined the correlation between the job satisfaction and organizational dependence and a cross sectional study is used. According to the conclusion of the poll, which has been carried out with all the employees in the corporation, which operates through the automotive sector, a significant correlation is found between the job satisfaction and organizational commitment.An increase of the inner satisfaction, outer satisfaction and general satisfaction, which are the sub-dimensions of the job satisfaction is detected, as the emotional commitment, continuance commitment and total organizational commitment,which are the sub-dimensions of the organizational commitment, increase. In this study is also attempted to determine, if the levels of the job satisfaction and the organizational commitment change according to the demographical factors. While no significant relation is found between the level of job satisfaction and the factors of gender,age, marital status and the duration of the actual job, a significant correlation has been detected between the level of the job satisfaction and the factors of gender, salary and position. No significant correlation between the level of organizational commitment and nd the factors of gender,age, marital status and the duration of the actual job, whereas a significant relation has been found between the level of organizational commitment and the factors of education, total length of the work, salary and position. Job Satisfaction, Organizational Commitment ABSTRACT THE RELATIONSHIP BETWEEN JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT: AN APPLİCATION This study examined the correlation between the job satisfaction and organizational dependence and a cross sectional study is used. According to the conclusion of the poll, which has been carried out with all the employees in the corporation, which operates through the automotive sector, a significant correlation is found between the job satisfaction and organizational commitment.An increase of the inner satisfaction, outer satisfaction and general satisfaction, which are the sub-dimensions of the job satisfaction is detected, as the emotional commitment, continuance commitment and total organizational commitment,which are the sub-dimensions of the organizational commitment, increase. In this study is also attempted to determine, if the levels of the job satisfaction and the organizational commitment change according to the demographical factors. While no significant relation is found between the level of job satisfaction and the factors of gender,age, marital status and the duration of the actual job, a significant correlation has been detected between the level of the job satisfaction and the factors of gender, salary and position. No significant correlation between the level of organizational commitment and nd the factors of gender,age, marital status and the duration of the actual job, whereas a significant relation has been found between the level of organizational commitment and the factors of education, total length of the work, salary and position.
Keywords: İş Tatmini; Örgütsel Bağlılık; Örgütsel Davranış